Permainan Ular Tangga Sebagai Media Edukasi Seksualitas Remaja - Edi, Edi; Taufik, M (Jurnal Endurance, 2019)
The age of adolescence is a period of transition from children to adulthood, where at this time there is a process of development and change both physically, emotionally and intellectually which is experienced as preparation for entering adulthood.  The lack of understanding of sexuality information directed will cause adolescents to take high risk actions for their own health.  One method that can be applied is sexuality education using the snake ladder game. One method that can be applied is sexuality education using the snake ladder game. The purpose of this study was to determine the effectiveness through the game of snakes and ladders as an educational media for adolescent sexuality in Hidayatul Muslimin 1 Kubu Raya Madrasah Ulya. This research is a quantitative research with pre-experimental design with one group pre and post test design approach. The number of samples are 120 respondents.  The sampling technique is purposive sampling.  Data were obtained using a questionnaire and analyzed by paired t test.  The results of the study showed that it was increasing in knowledge and attitudes towards the results of statistical analysis of knowledge which obtained a value of p = 0,000 <0,05.  As for the results of the attitude statistical analysis the value of p = 0,000 <0,05 was obtained. There is a significant relationship between the knowledge and attitudes of students with snake ladder sexuality media in Hidayatul Muslimin 1 Kubu Raya Madrasah Ulya.  Thus the snake ladder game can be used as an effective health education tool in changing knowledge and attitudesUsia remaja adalah masa peralihan dari anak-anak ke masa dewasa, dimana pada masa ini terjadi proses perkembangan dan perubahan baik fisik, emosional maupun intelektual yang dialami sebagai persiapan memasuki masa dewasa. Kurangnya pemahaman informasi seksualitas yang terarah maka akan menyebabkan remaja untuk melakukan tindakan berisiko bagi kesehatan mereka sendiri semakin meningkat. Salah satu metode yang bisa diterapkan adalah edukasi seksualitas menggunakan permainan ular tangga. Tujuan penelitian ini adalah untuk mengetahui efektivitas melalui permainan ular tangga sebagai media edukasi seksusalitas remaja di Madrasah Ulya Hidayatul Muslimin 1 Kubu Raya. Penelitian ini merupakan penelitian kuantitatif dengan desain pra eksperimen dengan pendekatan one group pre dan post test design. Jumlah sampel yaitu 120 responden. Teknik pengambilan sampel adalah purposive sampling. Data diperoleh dengan menggunakan kuesioner dan dianalisis dengan uji t berpasangan. Hasil penelitian menunjukkan bahwa ada peningkatan pengetahuan dan sikap terhadap hasil analisis statistik terhadap pegetahuan yang diperoleh nilai p = 0,000 <0,05. Sedangkan untuk hasil analisis statistik sikap diperoleh nilai p = 0,000 <0,05. Terdapat hubungan yang bermakna antara pengetahuan dan sikap siswa dengan media ular tangga seksualitas di Madrasah Ulya Hidayatul Muslimin 1 Kubu Raya. Dengan demikian permaian ular tangga dapat digunakan sebagai sarana edukasi kesehatan efektif dalam perubahan pengetahuan dan sikap